On Morpho-Syntax - Daniel Siddiqi (Universitat Autònoma de Barcelona, 2019)
This short paper offers a moment of reflection on the state of the Generative Grammar enterprise especially in light of the fact the Minimalist Syntax has so completely returned to a mission that includes (rather than explicitly excludes) a model of word-formation. I focus here on a discussion of crucial ways the move from “syntactic” theory to “morphosyntactic” theory has changed the mission of generative grammar and to what extent practitioners have kept pace. I hope to provide both a broad and a long view of metatheoretic concerns we now find ourselves at the nexus of and suggest best practices in light of those views.